2006
DOI: 10.1007/s10582-006-0563-y
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of 99-technetium in compacted bentonite under aerobic and anaerobic conditions

Abstract: The main aim of this study was to investigate diffusion of technetium 99 Tc under different conditions. Because technetium represents one of the most dangerous fission products due to its very long halftime and high mobility in aerobic conditions diffusion experiments of technetium (as 99 TcO 4 anion) in Czech bentonite from Rokle locality have been carried out. For performance and evaluation of experiments the through-diffusion method was chosen and apparent (D a ) and effective (D e ) diffusion coefficients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…All technetium isotopes are radioactive, and are produced by neutron fusion of 235 U in a small portion in nuclear reactors (10 -6 %), mainly by b-decay of fusion product 99 Mo (6 %). 99 Tc is released to the environment as pertechnetate [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All technetium isotopes are radioactive, and are produced by neutron fusion of 235 U in a small portion in nuclear reactors (10 -6 %), mainly by b-decay of fusion product 99 Mo (6 %). 99 Tc is released to the environment as pertechnetate [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption mechanism on AC is not fully known, however some of the results previously obtained indicate that the mechanism involves an anion exchange [10,11,14]. Yoshida et al [32] have attributed ion adsorption by active carbon to the chemical functional groups of chromene, pyrone and lactones present in the surface oxide of active carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Electromigration experiments indicated that D a for selenate is range from 1.7×10 -11 to 6.2×10 -11 m 2 s -1 and no reduction of selenate [4]. The degree of compaction is one of the important factors that influence the diffusion behavior of radionuclides in the clay [6]. Increasing clays compacting can change hydration energy, overlapping electric double layers and clay pore size and structure [7].…”
Section: Introductionmentioning
confidence: 99%